2022
DOI: 10.3390/ijerph19094991
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Induced by Changes in Proteomic Profiling of Zebrafish Chronically Exposed to a Mixture of Organochlorine Pesticides at Low Concentrations

Abstract: Effect of organochlorine pesticides (OCPs) mixtures on development of type 2 diabetes mellitus (T2DM) and the underlying mechanism, especially at protein levels, are largely unknown. We exposed a mixture of five OCPs to zebrafish at concentrations of 0, 0.05, 0.25, 2.5, and 25 μg/L for 12 weeks. Differentially expressed proteins (DEPs) were quantitatively identified in female zebrafish livers, and its functional study was conducted. The significantly high glucose and low insulin levels were observed only at 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
(63 reference statements)
0
2
0
Order By: Relevance
“…Individually, it has been observed that some OCP have diabetogenic effects at high doses to which humans would not normally be exposed [ 41 ]. More recently, it has been shown that OCP mixtures at low doses have diabetogenic effects through one or several mechanisms such as: the production of reactive oxygen species, mitochondrial dysfunction, insulin resistance, inhibition of insulin secretion, and alterations in lipid metabolism [ 42 45 ]. However, more information is required on the possible interactions between the underlying biological mechanisms of DM due to concomitant exposure to low doses of OCP.…”
Section: Discussionmentioning
confidence: 99%
“…Individually, it has been observed that some OCP have diabetogenic effects at high doses to which humans would not normally be exposed [ 41 ]. More recently, it has been shown that OCP mixtures at low doses have diabetogenic effects through one or several mechanisms such as: the production of reactive oxygen species, mitochondrial dysfunction, insulin resistance, inhibition of insulin secretion, and alterations in lipid metabolism [ 42 45 ]. However, more information is required on the possible interactions between the underlying biological mechanisms of DM due to concomitant exposure to low doses of OCP.…”
Section: Discussionmentioning
confidence: 99%
“…Glyceraldehyde 3-phosphate dehydrogenase expression is also decreased, which disturbs glucose homeostasis. These effects are caused by the proteome profiling of zebrafish livers using isobaric tags multiplexed quantitative proteomics [15].…”
Section: Computational Biology/toxicologymentioning
confidence: 99%